Phycosphere pH of unicellular nano- and micro- phytoplankton cells and consequences for iron speciation - Liu,F; Gledhill,M; Tan,Q-G; Zhu,K; Zhang,Q; Salaun,P; Tagliabue,A; Zhang,Y; Weiss,D; Achterberg,EP; Korchev,Y (The ISME Journal: multidisciplinary journal of microbial ecology, 2022)
Surface ocean pH is declining due to anthropogenic atmospheric CO2 uptake with a global decline of ~0.3 possible by 2100. Extracellular pH influences a range of biological processes, including nutrient uptake, calcification and silicification. However, there are poor constraints on how pH levels in the extracellular microenvironment surrounding phytoplankton cells (the phycosphere) differ from bulk seawater. This adds uncertainty to biological impacts of environmental change. Furthermore, previous modelling work suggests that phycosphere pH of small cells is close to bulk seawater, and this has not been experimentally verified. Here we observe under 140 μmol photons·m−2·s−1 the phycosphere pH of Chlamydomonas concordia (5 µm diameter), Emiliania huxleyi (5 µm), Coscinodiscus radiatus (50 µm) and C. wailesii (100 µm) are 0.11 ± 0.07, 0.20 ± 0.09, 0.41 ± 0.04 and 0.15 ± 0.20 (mean ± SD) higher than bulk seawater (pH 8.00), respectively. Thickness of the pH boundary layer of C. wailesii increases from 18 ± 4 to 122 ± 17 µm when bulk seawater pH decreases from 8.00 to 7.78. Phycosphere pH is regulated by photosynthesis and extracellular enzymatic transformation of bicarbonate, as well as being influenced by light intensity and seawater pH and buffering capacity. The pH change alters Fe speciation in the phycosphere, and hence Fe availability to phytoplankton is likely better predicted by the phycosphere, rather than bulk seawater. Overall, the precise quantification of chemical conditions in the phycosphere is crucial for assessing the sensitivity of marine phytoplankton to ongoing ocean acidification and Fe limitation in surface oceans.